"If we move, it moves with us:" Physical distancing in Africa during COVID-19. (June 2021) - Bicalho, Clara; Platas, Melina R.; Rosenzweig, Leah R.
Highlights: Even though 85% of respondents knew physical distancing helps curb the spread of COVID-19, over a third did not practice it. Increasing the salience of social or material costs of not practicing physical distancing had no effect on expected behavior. Respondents underestimated others' support for lockdown policies. Updating these beliefs may help encourage compliance. 54% of respondents wrote a message encouracing physical distancing, suggesting a potential tool for creating common knowledge. Abstract: Health behaviors to prevent the spread of infectious diseases are often subject to collective action problems, and social norms can play an important role in inducing compliance. In this paper, we study knowledge, beliefs, and behavior related to one such practice during the COVID-19 pandemic – physical distancing – using an online survey of social media users in Kenya, Nigeria, and Uganda. We find that, while there is widespread knowledge that physical distancing reduces the spread of the virus, respondents underestimate their peers' support for policies designed to enforce physical distancing, expect others not to practice physical distancing, and do not maintain physical distance themselves. However, more than half of respondents wrote a message to encourage others to practice physical distancing. Findings from survey experiments suggest that making salient the social and material costs for not keeping physical distance were insufficient to encourage compliance, suggestive of the absence of a social norm of physical distancing at the time. Given the large gap between own attitudes and expectations of others' attitudes toward lockdown policies, we propose that providing information on the extent of public support for physical distancing in citizens' own words may encourage compliance in the future.